Impact of Nasal Septum Deviation on Choroidal Thickness: Insights from A Clinical Study - Ahsan Qureshi, Rehan Moinuddin Shaikh, Muhammad Sharif Shahid, Muhammad Yousuf Memon, Liaquat Ali, Lal Muhammad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Nasal septum deviation (NSD) is a common otolaryngological condition that causes chronic nasal obstruction and hypoxia. Recent evidence suggests that systemic hypoxia and impaired vascular regulation may affect ocular physiology, particularly the choroidal circulation, which is critical for retinal function. Objective: The present study aimed to evaluate the impact of NSD on choroidal thickness and to explore its correlation with the severity of deviation. Methods: This hospital-based observational study was conducted from January 2022 to June 2023 at Mughal Eye Hospital, Lahore, and the ENT Department, CMH Sialkot. A total of 120 participants were enrolled, including 60 patients with clinically and radiologically confirmed NSD and 60 age- and sex-matched healthy controls. Ophthalmological assessment included best-corrected visual acuity, slit-lamp examination, intraocular pressure measurement, and enhanced depth imaging optical coherence tomography (EDI-OCT) to measure choroidal thickness at subfoveal, nasal (1500 µm), and temporal (1500 µm) points. Data were analyzed using SPSS v26, and statistical significance was set at p < 0.05. Results: Patients with NSD demonstrated significantly reduced choroidal thickness compared to healthy controls. Mean subfoveal thickness was 258.4 ± 21.7 µm in the NSD group versus 287.6 ± 18.5 µm in controls (p < 0.01). Nasal and temporal thicknesses were also significantly lower in NSD patients (236.2 ± 20.1 µm and 242.6 ± 21.3 µm, respectively) compared to controls (265.3 ± 18.8 µm and 270.4 ± 17.2 µm; p < 0.01). A moderate negative correlation (r = –0.42, p = 0.03) was found between severity of deviation and subfoveal thickness. Conclusion: Nasal septum deviation is associated with significant thinning of the choroid, and the degree of reduction correlates with the severity of deviation. These findings suggest that chronic nasal obstruction and hypoxia may compromise ocular vascular integrity. Early recognition and interdisciplinary management involving otolaryngologists and ophthalmologists are recommended. Keywords: nasal septum deviation, choroidal thickness, optical coherence tomography, hypoxia, ocular circulation